(untitled) (Research, Society and Development, 2024)
This article is the result of Undergraduate Research financed by PIBIC Institution Program of Scientific Initiation Scholarships and developed by medical students alongside integrants of a rehabilitation housing program. The Research consisted in the integrants of there habilitation house writing letters relating their life experiences, history of drug abuse and treatment of this issue. It’s a qualitative and descriptive research, which is being done by phases. From the 44 written letters, five of them were chosen, based on its length of your content, for this analysis. The remaining ones were saved for another phase of the process. The support theory chosen for the research was the "spiritual intelligence" to the strands of Torralba, Zohar and Marshall. It is important to emphasize that spiritual intelligence is not limited to religion, but above all in the search for the meaning of life and the individual capacity to find oneself in the world. Therefore, the objective of this article is to analyze and present, in a qualitative and descriptive way, the contribution of spiritual intelligence in the chemical recovery process. This, the study aimed to analyze the contribution of spiritual intelligence in the process of chemical recovery. The results showed the important role of there habilitation housing programan to the development of the spiritual intelligence, which, contributs to the rehabilitation processes.